Seroprevalence of hepatitis B and hepatitis C markers in adolescents in Southern Brazil Soroprevalência de marcadores de hepatite B e hepatite C em adolescentes no Sul do Brasil - Natália Gazzoni Scaraveli; Ana Maria Passos; Andréia Royer Voigt; Andréa do Livramento; Gabriela Tonial; Aricio Treitinger; Celso Spada (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This study was carried out to determine the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) markers among adolescents aged between 10 and 16 years old, who are elementary school students in the city of Chapecó, Santa Catarina State, Brazil. The study involved a cross-sectional survey that included 418 volunteers, from March to July, 2008. Serology comprised HBsAg, anti-HBc, anti-HBs and anti-HCV. Tests were performed using automated Microparticle Enzyme Immunosorbant Assay (Abbott, AxSYM System, Wiesbaden, Germany). The prevalence of HBsAg was found to be 0.2% (95%CI: 0.0-1.3), and the prevalence of anti-HBc was found to be 1.4% (95%CI: 0.5-3.1). Regarding anti-HBs, 48.6% had titers greater than 10UI/L. None of the volunteers presented reactive results for anti-HCV. This study showed a low prevalence of HBV and HCV markers of infection and a great number of volunteers immunized against HBV. Finally this study shows the importance of proper health campaigns and policies in reducing those prevalences. Este estudo teve como objetivo determinar a prevalência de marcadores do vírus da hepatite B (HBV) e do vírus da hepatite C (HCV) entre adolescentes com idade entre 10 e 16 anos, alunos do Ensino Fundamental da cidade de Chapecó, Santa Catarina, Brasil. Trata-se de um estudo transversal incluindo 418 voluntários, realizado entre março e julho de 2008. As análises sorológicas incluíram: HBsAg, anti-HBc, anti-HBs e anti-HCV. Os testes foram realizados em Ensaio Enzimático de Micropartículas (Abbott, AxSYM System, Wiesbaden, Alemanha). A prevalência de HBsAg foi de 0,2% (IC95%: 0,0-1,3), e a prevalência de anti-HBc foi de 1,4% (IC95%: 0,5-3,1). Quanto ao anti-HBs, 48,6% dos voluntários apresentaram títulos maiores que 10UI/L. Nenhum dos voluntários apresentou resultados reativos para anti-HCV. Este estudo demonstrou uma baixa prevalência de marcadores de infecção HBV e HCV e um grande número de voluntários imunizados contra o HBV. Finalmente, demonstrou-se a importância de campanhas e políticas adequadas de saúde na redução dessas prevalências.